Personal transferable skills in accounting education - Watty, Kim; Jackling, Beverley; Wilson, R. M. S. (Richard Malcolm Sano) (Routledge, 2012)
The development of generic skills (often referred to as 'soft skills') in accounting education has been a focus of discussion and debate for several decades. During this time employers and professional bodies have urged accounting educators to consider and develop curricula which provide for the development and assessment of these skills. In addition, there has been criticism of the quality of accounting graduates and their ability to operate effectively in a global economy. Embedding generic skills in the accounting curriculum has been acknowledged as an appropriate means of addressing the need to provide 'knowledge professionals' to meet the needs of a global business environment.